2022
DOI: 10.1093/nar/gkac933
|View full text |Cite
|
Sign up to set email alerts
|

CAMPR4: a database of natural and synthetic antimicrobial peptides

Abstract: There has been an exponential increase in the design of synthetic antimicrobial peptides (AMPs) for its use as novel antibiotics. Synthetic AMPs are substantially enriched in residues with physicochemical properties known to be critical for antimicrobial activity; such as positive charge, hydrophobicity, and higher alpha helical propensity. The current prediction algorithms for AMPs have been developed using AMP sequences from natural sources and hence do not perform well for synthetic peptides. In this versio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 63 publications
0
34
0
Order By: Relevance
“…Additionally, as the work by Tucs et al . on AMPs (PepGAN) showed that most of their new peptides were cationic and amphiphilic, and to enrich the training sets for GAN, sequences from their data sets (retrieved from Antimicrobial Peptide Database (APD), Collection of Anti-Microbial Peptides (CAMP), Linking Antimicrobial Peptides (LAMP), and Database of Antimicrobial Activity and Structure of Peptides (DBAASP) databases) were also collected. Sequences with up to 52 amino acids were used for training, and redundant sequences were removed.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, as the work by Tucs et al . on AMPs (PepGAN) showed that most of their new peptides were cationic and amphiphilic, and to enrich the training sets for GAN, sequences from their data sets (retrieved from Antimicrobial Peptide Database (APD), Collection of Anti-Microbial Peptides (CAMP), Linking Antimicrobial Peptides (LAMP), and Database of Antimicrobial Activity and Structure of Peptides (DBAASP) databases) were also collected. Sequences with up to 52 amino acids were used for training, and redundant sequences were removed.…”
Section: Methodsmentioning
confidence: 99%
“…Various resources have been employed to offer information and sequences of AVPs. , However, DBAASP stands out, as it presents the annotation of the virus entry inhibitory activity in the most user-friendly and convenient form. Therefore, target viruses were chosen from DBAASP or from the literature, and information on sequences and structures of the envelope proteins was acquired from Uniprot, PDB Bank, and Genbank …”
Section: Methodsmentioning
confidence: 99%
“…More than 3000 naturally occurring antimicrobial peptides have been identified, and there is a database containing 24,243 natural and synthetic antimicrobial peptides [ 106 ]. More than 60 antimicrobial peptides have been approved by the FDA [ 107 ]. The natural antimicrobial peptides are susceptible to proteolytic degradation and are hemolytic [ 108 , 109 ].…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%